Kohlraush thermal relaxation in a random magnet - COEY, JOHN MICHAEL DAVID (American Physical Society, 1987)
Specific-heat measurements on amorphous FexZr100-x (x=90 and 92) by a thermal relaxation method reveal a temperature decay of the form T(t)=T0+T exp[-(t/)] below 20 K, where the alloys are asperomagnetically ordered. 0.5 when T00. The stretched exponential is a manifestation of nonergodic behavior, because of the inability of the spin system to explore the available random magnetic configurations on the 100-ms times scale of the experiment.
PUBLISHED
Keywords: Physics